Obtaining superhard composites in the system Cdiam—SiB4—WC under conditions of high pressures and temperatures - Stratiichuk, D.A.; Turkevich, V.Z.; Bushlya, V.M. (Reports of the National Academy of Sciences of Ukraine, 2019)
Under conditions of high pressures (7.7 GPa) and temperatures (1600-2200 0C) in a high-pressure apparatus of the “toroid-30” type, sintering of diamond micropowders in the presence of silicon tetraboride (SiB4) and tungsten carbide is studied. It is experimentally shown that SiB4 and WC additives in the amount of 5 % by volume each are quite sufficient for the formation of a durable diamond composite, and the reaction sintering process is best carried out in the temperature range 1900-2000 0C with an exposure time of no more than 60 sec. According to the XRD analysis, it is shown that, at temperatures above 1600 0C, silicon tetraboride interacts with diamond carbon and WC, resulting in the formation of β-SiC and W2B5 phases, which are concentrated in the intergranular space and are the connecting phases of the diamond composite. At temperatures above 2200 0C, the significant graphitization of diamond grains is recorded, and, as a consequence, a sharp drop in the physicomechanical characteristics of the composite is observed. The material obtained at 1950 0C is characterized by low porosity ( 0.1%), high hardness (HV10 = 62 GPa), crack resistance (K1C = 9.7 MPa · m1/2), Young’s modulus equal to 820 GPa, and heat resistance 1100 0C.